Putting the fragments (back) together: towards a theorisation of Jewish sampling. (4th May 2017) - Stratton, Jon
ABSTRACT: This article argues that there is an elective affinity between the Jewish worldview and sampling. Sampling has a history much longer than its use in hip hop. Here, though, I am concerned with Jewish artists who have used sampling since the 1980s such as Steinski, the Beastie Boys, Edan and SoCalled. These artists have worked within the generic form of hip hop but have created texts that are quite distinct from texts created by African Americans. My list here is by no means definitive but is a function of the artists that I use for illustrative purposes. I suggest that the Jewish worldview, founded on ideas of catastrophe and exile, and of the bringing back together of fragments to form a new cultural whole, has a synergy with sampling which utilises fragments in the service of creating a new text. These reference points are different from the assumptions that underpin African-American uses of hip hop.